Modified intratympanic steroid therapy for sudden sensorineural hearing loss via tympanic tube and gelfoam as a salvage treatment - Sichao Liang; Yunshuo Li; Zhenping Guo; Manlin Lu; Xin Li; Jia Xu; Wenjing Chen; Juanjuan Gao; Haijin Yi (Journal of Otology, 2024)
Background: Sudden sensorineural hearing loss (SSNHL) is a prevalent emergency in ear, nose, and throat practice. Previous studies have demonstrated that intratympanic steroid therapy (IST) can serve as a salvage treatment for SSNHL after the failure of systemic steroid therapy (SST). Objective: This study aimed to analyze the efficacy of modified IST involving the insertion of a tympanic tube and gelfoam as a salvage treatment for patients with SSNHL, and to explore its associated factors. Methods: Totally, 74 patients who were aged 22–81 years with SSNHL were enrolled and allocated to either the control group (n = 25) or the treatment group (n = 49) based on their treatment modalities. All patients received SST lasting for at least 7 days. Subsequently, patients in the treatment group, after SST failure, underwent IST twice a week for 2–6 weeks, while the control group did not. Efficacy was assessed by the improvement in pure tone average at the affected frequency at the beginning and end of IST. Results: Hearing improvement in all patients after IST in the treatment group was 9.71 ± 14.84 dB, with significant improvement at affected frequencies (250-8000 Hz) compared with the control group (P < 0.05). The findings indicated the duration from the onset of SSNHL to the beginning of IST as an independent factor for pure tone average improvement after treatment (P = 0.002), whereas age, duration of SST, and time of IST were not (P > 0.05). Conclusion: The modified IST was demonstrated to be a safe and effective method as a salvage treatment for SSNHL. This study explored the efficacy of a modified IST approach, incorporating the utilization of tympanic tubes and gelfoam as key components. The findings underscore the advantages of gelfoam as a strategic drug carrier placed in the round window niche. By minimizing drug loss, extending action time, and increasing perilymph concentration, gelfoam enhances the therapeutic impact of IST, contributing to improved hearing outcomes in patients with SSNHL.